An assessment of technical feasibility and interannual variability for utility scale wind energy development at five favourable locations in Myanmar - Htike, Thein Min; Soe, Paing Hein; Phyo, Mi Zwe Mon (My University, 2026)
Myanmar’s projected electricity demand of 14.542 GW by 2030 and its Intended Nationally Determined Contribution (INDC) underscore the necessity of diversifying the national energy mix to enhance environmental sustainability. Solar and wind energy are targeted to contribute 9% of the total installed capacity. Consequently, a reliable assessment of renewable resources is essential for guiding investment and policy decisions. Although prior studies have mapped wind speed and power density, detailed analyses of the spatial and temporal variability of wind resources for energy production remain limited. This study evaluates wind conditions using 2010–2017 ERA5 data, focusing on mean wind speed, power density, predominant wind direction, and temporal variations at yearly, seasonal, monthly, and diurnal scales. Crucially, this work extends traditional assessments by quantifying wind persistence through autocorrelation and evaluating the Interannual Variability (IAV) of Annual Energy Production (AEP) to assess meteorological risks. Five potential locations were selected for detailed analysis using two utility-scale turbines. Annually, hours with wind speeds exceeding 6 m/s account for 23.21–35.08%, while hours with wind speeds exceeding 4 m/s represent 50.26–64.29%. Results identify Ngapudaw (Ayeyarwaddy) as the most favorable site, with an average AEP of 5.05 GWh, a capacity factor of 23.08%, and a moderate risk profile (7.83% IAV). While coastal site Sittwe exhibits high energy potential, it also presents greater interannual fluctuations (9.10% IAV); in contrast, inland sites like Wundwin offer exceptionally stable resources with an IAV < 5%. This quantitative assessment confirms the technical viability of wind power in Myanmar and supports further exploration of site-specific opportunities to expand renewable energy deployment. These findings provide a foundational justification for stakeholders, including investors and policymakers, to advance wind farm development, contributing to Myanmar’s environmental protection and sustainability goals in alignment with UN Sustainable Development Goals (SDGs) 7 (Affordable and Clean Energy) and 13 (Climate Action).
Keywords: Annual energy production; Capacity factor; Myanmar; Renewable energy; Seasonal wind variations; Sustainable development; Wind power potential; Wind resource assessment